DNA Polymerases η and ζ Combine to Bypass O(2)-[4-(3-Pyridyl)-4-oxobutyl]thymine, a DNA Adduct Formed from Tobacco Carcinogens - Gowda, A. S. Prakasha (Chem Res Toxicol, 2016)
4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and N′-nitrosonornicotine (NNN) are important human carcinogens in tobacco products. They are metabolized to produce a variety 4-(3-pyridyl)-4-oxobutyl (POB) DNA adducts including O(2)-[4-(3-pyridyl)-4-oxobut-1-yl]thymidine (O(2)-POB-dT), the most abundant POB adduct in NNK- and NNN-treated rodents. To evaluate the mutagenic properties of O(2)-POB-dT, we measured the rate of insertion of dNTPs opposite and extension past O(2)-POB-dT and O(2)-Me-dT by purified human DNA polymerases η, κ, ι, and yeast polymerase ζ in vitro. Under conditions of polymerase in excess, polymerase η was most effective at the insertion of dNTPs opposite O(2)-alkyl-dTs. The time courses were biphasic suggesting the formation of inactive DNA-polymerase complexes. The k(pol) parameter was reduced approximately 100-fold in the presence of the adduct for pol η, κ, and ι. Pol η was the most reactive polymerase for the adducts due to a higher burst amplitude. For all three polymerases, the nucleotide preference was dATP > dTTP ≫ dGTP and dCTP. Yeast pol ζ was most effective in bypassing the adducts; the k(cat)/K(m) values were reduced only 3-fold in the presence of the adducts. The identity of the nucleotide opposite the O(2)-alkyl-dT did not significantly affect the ability of pol ζ to bypass the adducts. The data support a model in which pol η inserts ATP or dTTP opposite O(2)-POB-dT, and then, pol ζ extends past the adduct.